Numerical study of oil–water emulsion formation in stirred vessels: effect of impeller speed. (24th November 2022) - Liang, Fuyue; Kahouadji, Lyes; Valdes, Juan Pablo; Shin, Seungwon; Chergui, Jalel; Juric, Damir; Matar, Omar K
Abstract: Abstract : The mixing of immiscible oil and water by a pitched blade turbine in a cylindrical vessel is studied numerically. Three-dimensional simulations combined with a hybrid front-tracking/level-set method are employed to capture the complex flow and interfacial dynamics. A large eddy simulation approach, with a Lilly–Smagorinsky model, is employed to simulate the turbulent two-phase dynamics at large Reynolds numbers $Re=1802{-}18\ 026$ . The numerical predictions are validated against previous experimental work involving single-drop breakup in a stirred vessel. For small $Re$, the interface is deformed but does not reach the impeller hub, assuming instead the shape of a Newton's Bucket. As the rotating speed increases, the deforming interface attaches to the impeller hub which leads to the formation of long ligaments that subsequently break up into small droplets. For the largest $Re$ studied, the system dynamics becomes extremely complex wherein the creation of ligaments, their breakup and the coalescence of drops occur simultaneously. The simulation outcomes are presented in terms of spatio-temporal evolution of the interface shape and vortical structures. The results of a drop size analysis in terms of the evolution of the number of drops, and their size distribution, is also presented as a parametric function of $Re$ .